Acute Mania and Catatonia in a Teenager Successfully Treated with Electroconvulsive Therapy and Diagnosed with Turner Syndrome and Bipolar Disorder - Maria Ygland Rödström; Björn Axel Johansson; Beata Bäckström; Pouya Movahed; Carl-Magnus Forslund; Olof Rask (Case Reports in Psychiatry)
Background. Turner syndrome (TS) is an X-linked chromosomal abnormality with a global prevalence of 1/2000 live-born girls. The physiological symptoms of TS have been thoroughly characterized, but only a few studies have described associated psychiatric symptoms. We report a case of an adolescent girl who presented with acute mania with psychotic features and was successfully treated with electroconvulsive therapy (ECT). She was subsequently diagnosed with bipolar syndrome and TS. Case Presentation. A 17-year-old girl presented to us with manic symptoms, including disorganized speech, auditory hallucinations, and affect lability. Initially, she was treated with antipsychotics and benzodiazepines, whereby the positive affective symptoms declined. However, the psychotic symptoms progressed, and she developed a catatonic state. ECT was started 6 days after admission, with improvement after two treatments. When ECT was tapered after seven sessions, she relapsed, and the treatment was extended to twelve sessions, with successful outcome. Following discharge, she was diagnosed with TS with partial loss on one of the X-chromosomes (46X, del (X)(p21)), which might have contributed to the development of her sudden acute manic episode. Conclusions. This case demonstrates for the first time that ECT may be a safe and efficient treatment strategy for acute mania in adolescents with concomitant TS and that severely affected adolescents may require a prolonged series with gradual tapering of ECT. The present case also demonstrates a possible association between TS and bipolar syndrome and that the clinical presentation of a manic episode in a patient with this comorbidity could be more complex and the treatment response slower.